Alternatives control strategies for Building Integrated Photovoltaic/Thermal (BIPVT) system - Abdul Wahab, H; Duke, M; Carson, JK; Anderson, TN (Universiti Tun Hussein Onn Malaysia, 2012)
The use of energy in buildings is an ongoing concern, not only in NZ but worldwide. This concern has led to significant growth in the use of solar energy to provide heating and electricity generation. This paper presents the theoretical and experimental results of a novel building integrated solar hot water system; developed using commercial, long run roofing materials. This work shows that it is possible to achieve effective integration that maintains the aesthetics of the building. Building integrated thermal (BIT) system parameters are identified and implemented in the TRansient SYstem Simulation (TRNSYS) modeling environment. Validation result comparing the simulation in TRNSYS and real experimentation show that experimental and simulation responses are close to each other. The coupling of TRNSYS and Matlab/Simulink shows the possibility to use Matlab/Simulink for developing appropriate control strategies for BIT roofing systems. Furthermore in this paper, a Fuzzy Logic (FL) controller is implemented in a Fuzzy Integrated System (FIS) toolbox in a Matlab/Simulink model and linked into TRNSYS building integrated photovoltaic/thermal (BIPVT) system model. Preliminary simulation results are presented, which showed that the FL control strategies improved the energy performance of the BIPVT system and could be an effective way controlling building integrated solar energy systems.